Psychological analysis of sociogram and biographical method for investigating parents of children with special educational needs - Andreyko, Bohdana; Subashkevych, Iryna (Journal of Education Culture and Society, 2020)
Aim. In order to provide psychological counselling, it is necessary to properly diagnose and study the psycho-emotional states, psychological makers of parents raising children with special educational needs (SEN).Methods. In the diagnostic and practical work with parents of children with SEN, we used the text analysis method and the biographical method (including projective techniques lifeline, my autobiography), which combine diagnostic and psychotherapeutic scientific results. Family sociogram technique (Eidemiller, 2002) and its modified version (Tkachova, 2014) are used to study interpersonal family relationships and the nature of communication. The article analyses the scientific data and approaches to the study of problems faced by parents, arising from the condition of their child; emotional states of parents raising a child with SEN; stage of experience of the birth of their child.Results. Intervention is focused on the present and future. If the experience of the past comes up, it is used for the benefit of achieving certain goals. An important result of the study to be worked on is that parents of special children mention only their family and children, but forget about their own wellbeing. Children with SEN are surrounded by care and love, parents seek symbiotic relationships with children trying to satisfy all their needs, protect from difficulties, offer boundless love and sometimes over-protection.Conclusion. Knowledge of psychological stages identified within the theory of grief helps professionals understand when and how it is better to intervene in the situation taking into account the characteristics of a particular family and individual reactions.